Mohiniyattam - Shivaji, Bharati; Pasricha, Avinash; Vijayalakshmi (New Delhi : Wisdom Tree, 2004)
In this book, the actual practitioners of Mohiniyattam forms, the dancers themselves, give the insider's point of view, the origin and history, the music, the costumes, make-up and specific jewellery
Keywords: Dance -- Kerala -- India; Mohiniyattom (Dance) -- Kerala -- India; Dance -- Kerala -- India -- Origin; Dance -- Kerala -- India -- Equipments and supplies